GPS precise point positioning for UAV photogrammetry. (5th November 2018) - Grayson, Ben; Penna, Nigel T.; Mills, Jon P.; Grant, Darion S.
Abstract: The use of Global Positioning System (GPS) precise point positioning (PPP) on a fixed‐wing unmanned aerial vehicle (UAV) is demonstrated for photogrammetric mapping at accuracies of centimetres in planimetry and about a decimetre in height, from flights of 25 to 30 minutes in duration. The GPS PPP estimated camera station positions are used to constrain estimates of image positions in the photogrammetric bundle block adjustment, as with relative GPS positioning. GPS PPP alleviates all spatial operating constraints associated with the installation and the use of ground control points, a local ground GPS reference station or the need to operate within the bounds of a permanent GPS reference station network. This simplifies operational logistics and enables large‐scale photogrammetric mapping from UAVs in even the most remote and challenging geographic locations. Abstract : Global Positioning System (GPS) precise point positioning (PPP) constraints on fixed‐wing unmanned aerial vehicle (UAV) image positions is demonstrated for photogrammetric mapping at accuracies of centimetres in planimetry and about a decimetre in height, from flights of 25‐30 minutes duration. GPS PPP alleviates all spatial operating constraints associated with the installation and use of ground control points, simplifying operational logistics and enabling large‐scale photogrammetric UAV mapping even in the most remote and challenging geographic locations.